KAJIAN PUSTAKA JENIS STARTER, LAMA FERMENTASI, DAN SIFAT ORGANOLEPTIK YOGHURT SUSU KEDELAI - Lina Mufidah; Eka Rachmawati; Christiana Mayang (Jurnal Socia Akademika, 2021)
Fermented dairy products by bacterial microbes called Yogurt, this fermentation of lactose produces lactic acid that works on milk proteins so that yoghurt has a distinctive texture, flavour, and aroma. In general, yoghurt is made using cow's milk, but the advancement of yoghurt biotechnology can also be made from vegetable milk among others from soybeans. Soybeans have a distinctive aroma langu that results in a decrease in acceptability in the community. The smell of langu is produced from the formation of volatile carbonyl compounds during the catalyst of polyunsaturated fatty acids by lipoxygenase. The purpose of this literature review is to find out the type of starter, the length of fermentation of soy milk and also its organoleptic properties. The research method used is a literature review. This method collects library data or research documents obtained from scientific journals and electronic searches including two databases, Pubmed, and Google Scholar issue 2011-2021 that can be accessed in full text in pdf format. The results of the study on average every 1 gr/cc starter made with soy milk with a size of 200 ml. Starters often used in the manufacture of soy milk yoghurt are Lactobacillus bulgaricus and Streptococcus thermophilus. The duration of fermentation depends on the starter used and also depends on the mixture of soy milk ingredients. The average fermentation time is 10.5 hours (7-15 hours). organoleptic soy yoghurt will be accepted on the characteristics of odourless aroma, non-viscous texture and not too sour taste. Soy yoghurt is more accepted with the addition of fruit and also dates